Revitalizing the Meaning of Nias Language Proverbs as Character Building for EFL Learners in Nias - Lecisia Zagoto; Mega Riahta Bancin; Thresia Anita Sari Saragih; Azizah Husda , S.S., M.Hum (English Language Teaching Prima Journal (ELT), 2021)
Abstract This study aims to uncover what extent of the Revitalizing the Meaning of Nias Language Proverbs as Character Building foe EFL Learners in Nias. In conducting this research, the research designis Ethnography is a type of qualitative research design. To collect the data, the study employs the interviews with 5 question and observation given to 30 students from gradeXI MIA 1. The research conducted in SMA Negeri 1 Luahagundre. This study investigates of Nias language proverbs as character buildingwith four types of character according by (Khan, 2010), there are; Moral conservation, Social conservation, Environmental conservation, and Human conservation. As a result of the study, the student experiences a change in character after learning Amaedola in the classroom for example there are previous students whose words are offensive and researchers provide Amaedola as the learning process goes on about amuata nifaigi ba bua-bua nitӧngӧni which means a person is evaluated by his behavior and the manner of his work. The researchers have found that taught Amaedola can motivate the students to achieve knowledge and good character. Researchers found benefits for teachers in the application of amaedola or proverbs to establish character and motivate students to attain their goals. Keywords: character building, proverbs Nias, value, EFL